(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Moving from Institutionalism, as a general legal theory developed by Santi Romano and Maurice Hauriou, the paper examines the juridical category of total institutions. In those contexts, constitutional liberties are radically limited since the individual becomes part of the institution and the separation between the person and the authority is erased. The following step is to examine the juridical meaning of the word «deinstitutionalization». The term has been introduced by law no. 227/2021, as a guideline for the new legal discipline concerning disability.